Synchronous and Time-Dependent Expression of Cyclins, Cyclin-Dependant Kinases, and Apoptotic Genes in the Rumen Epithelia of Butyrate-Infused Goats - Soomro, Jamila; Lu, Zhongyan; Gui, Hongbing; Zhang, Bei; Shen, Zanming (Frontiers in Physiology, 2018)
In our previous study, we demonstrated that butyrate induced ruminal epithelial growth through cyclin D1 upregulation. Here, we investigated the influence of butyrate on the expression of genes associated with cell cycle and apoptosis in rumen epithelium. Goats (n= 24) were given an intra ruminal infusion of sodium butyrate at 0.3 (group B, n = 12) or 0 (group A, n = 12) g/kg of body weight (BW) per day before morning feeding for 28 days and were slaughtered (4 goat/group) at 5,7 and 9 h after butyrate infusion. Rumen fluid was analyzed for short chain fatty acids (SCFAs) concentration. Ruminal tissues were analyzed for morpho-histrometry and the expressions of genes associated with cell cycle and apoptosis. The results revealed that the ruminal butyrate concentration increased (P < 0.05) in B compared to group A. Morphometric analysis showed increased (P < 0.05) papillae size associated with higher number of cell layers in epithelial strata in B compared to A. Butyrate-induced papillae enlargement was coupled with enhanced mRNA expression levels (P < 0.05) of cyclin D1, CDK2, CDK4 and CDK6 (G0/G1 phase regulators) at 5 h, cyclin E1 (G1/S phase regulator) at 7 h and cyclin A and CDK1 (S phase regulators) at 9 h post-infusion compared to A group. In addition, the mRNA expression levels of apoptotic genes i.e. caspase 3, caspase 9 and Bax at 5 h post-infusion were upregulated (P < 0.05) in group B compared to group A. The present study demonstrated that butyrate improved ruminal epithelial growth through concurrent and time-dependent changes in the expressions of genes involved in cell proliferation and apoptosis. It seems that the rate of proliferation was higher than the apoptosis which was reflected in epithelial growth.